2017
DOI: 10.1016/j.jpain.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pain Catastrophizing on Outcomes: A Developmental Perspective Across Children, Adolescents, and Young Adults With Chronic Pain

Abstract: Pain catastrophizing is one of the most powerful predictors of poor outcomes in youth and adults with pain; however, little is known about differential impacts of pain catastrophizing on outcomes as a function of age. The current study examined the predictive value of pain catastrophizing on pain interference and pain intensity across children, adolescents, and two age groups of young adults with chronic pain. Cross-sectional data are presented from the adult and pediatric Collaborative Health Outcomes Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 69 publications
2
45
0
1
Order By: Relevance
“…Future research can also examine how age and stage of cognitive development may impact associations among catastrophizing and pain outcomes in youth with acute pain. Recent data within a pediatric chronic pain sample found pain catastrophizing was more strongly associated with disability in adolescents compared to younger children [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Future research can also examine how age and stage of cognitive development may impact associations among catastrophizing and pain outcomes in youth with acute pain. Recent data within a pediatric chronic pain sample found pain catastrophizing was more strongly associated with disability in adolescents compared to younger children [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Pain is a global health problem with broad negative impacts on physical (Sturgeon, Darnall, Kao, & Mackey, 2015; Sturgeon, Dixon, Darnall, & Mackey, 2015), mental (Bair, Robinson, Katon, & Kroenke, 2003; Feinstein et al, 2017; Ziadni, Sturgeon, & Darnall, 2018), spiritual (Halawa, Al-Diri, McLean, & Darnall, 2015), psychosocial (Karos, Meulders, Goubert, & Vlaeyen, 2018; Karos, Williams, Meulders, & Vlaeyen, 2018; Sturgeon et al, 2016; Ziadni, You, Wilson, & Darnall, 2018), and economic domains (Groenewald, Essner, Wright, Fesinmeyer, & Palermo, 2014; Gustavsson et al, 2012). The 2016 Institute of Medicine report on Relieving Pain in America estimated that roughly one-third of the world population is living with ongoing pain of some type (IOM Committee on Advancing Pain Research, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, children typically have less familiarity of being in pain, so they register pain more emotionally. This hypothesis was confirmed by Feinstein et al (2017), who found that for children, emotional-distress predicted PC, but for adults, pain-intensity predicted PC.…”
Section: Contributing So Cial Fac Tor Smentioning
confidence: 63%